Factors associated with autism severity in children with autism spectrum disorder at an autism intervention center in Kuala Lumpur, Malaysia - Eow, Shiang Yen (2019)
Autism is a life-long neurodevelopmental condition that affects the ability of a person to communicate and relate to others. Its symptoms can be conceptualized along a continuum ranging from mild to severe expression. Children with Autism Spectrum Disorder (ASD) of higher symptom severity exhibit different behaviors and characteristics compared to their counterparts of lower symptom severity. To date, there is limited nutrition-related study in children with ASD of different autism severity in Malaysia. Most of the previous local studies on ASD in Malaysia focused on education, engineering, information technology, medical, and psychology. Therefore, this cross-sectional study aimed to determine the associations between sociodemographic factors, parental factors, and lifestyle factors with autism severity in children with ASD at a selected autism intervention center in Kuala Lumpur. A total of 224 children with ASD (82.6% boys and 17.4% girls) with a mean age of 5.19 ± 0.87 years and their mothers participated in this study. Mothers completed a self-administered questionnaire on sociodemographic background, autism severity, parenting style, parental feeding practices, parenting stress, child sleep habits, and child eating behaviors. A 3-day food diary was recorded by the mothers at home to determine dietary adequacy of their children. Body weight and height of the children were measured by the researcher in the center. The Social Communication Questionnaire (SCQ) was used to measure autism severity. Results showed that the mean score of the SCQ was 20.12 ± 6.93, ranging from 3 to 38. Majority of the children with ASD in this study (78.1%) were in the high level of autism severity. In term of nutritional status, the prevalence rates of underweight, stunting, wasting/thinness, and overweight/obesity were 9.3%, 8.0%, 4.0%, and 21.5%, respectively. More than half of the children with ASD did not meet the recommended nutrient intake (RNI) requirement for fiber (99.6%), thiamin (67.4%), and calcium (90.2%). Most of the mothers (94.6%) practiced authoritative parenting style, which is characterized by reasonable demands and high responsiveness. Multiple linear regression results showed that mother’s educational level (B=6.185, 95% CI=2.389, 9.982, p=0.002), father’s employment status (B=2.912, 95% CI=0.917, 4.906, p=0.004), perceived child weight (B=2.912, 95% CI=0.917, 4.906, p=0.004), concern about child weight (B=1.111, 95% CI=0.139, 2.083, p=0.025), total fiber intake (B=-0.297, 95% CI=-0.569, -0.026, p=0.032), and sodium intake (B=0.001, 95% CI= 0.0001, 0.002, p=0.044) predicted autism severity among children with ASD in this study. These six variables accounted for a significant 19.6% of the variability in autism severity (F=8.773, p<0.001; R2=0.196, Adjusted R2=0.174). In conclusion, children with ASD in this study reported high level of autism severity. More parental involvement and time spent with children with ASD should be encouraged to promote better parent-child interactions. Nutrition education programs for parents should emphasize healthy child weight management, healthy eating and parenting practices in order to improve ASD symptomatology and to ensure optimal growth of children with ASD.